High‐Speed Rail and Rural Livelihood: The Wuhan‐Guangzhou Line and Qiya Village. (27th November 2015) - Liu, Shujing; Kesteloot, Christian
Abstract: China has started to develop the world's largest high‐speed rail network in the twenty‐first century with the general aims of developing the economy and increasing environmental sustainability. Meanwhile economic reforms have created massive movements of rural workers towards urban labour markets. The co‐existence of these movements with a HSR network raises the question about the impacts of the HSR on rural migrants and the livelihoods in their villages. This paper seeks to analyse these impacts from a livelihood perspective. Two main roles of transport are analysed: transport as delivering access to new economic opportunities and transport as an industry providing employment. Statistical data and fieldwork evidence in Qiya, a small village in Hunan province, show that the opening of the Wuhan‐Guangzhou HSR line decreased their access to places of employment both in terms of cost and time, but the HSR construction created employment opportunities for the villagers.